Effects of capital market development on inflow of foreign direct investment to African countries - Aregbeshola, Rafiu Adewale (My University, 2014)
The role of foreign direct investment (FDI) in economic growth is well documented in the literature. Various studies have established that FDI contributes both directly and indirectly to economic growth of the host country, especially, in the developing countries. Despite the proven benefits of FDI to developing countries, Africa continues to account for less than six per cent of the global stock of FDI. To uncover why developing countries (especially countries in Africa) are less attractive to inflow of FDI, a number of studies have been conducted. In most of those studies, the role of macroeconomic fundamentals is presented as the major hindrance to the developing world in attracting FDI. However, the fact that some developing countries (particularly in Asia and South America) falter on these considerations and still manage to attract inflow of FDI begs the straightjacket validity and appropriateness of those postulations. This new line of thought motivates the interest in looking at other set of variables that are capable of influencing the attractiveness of countries (especially developing countries like those in Africa) to inflow of FDI. This study investigates the effects of capital market development on inflow of FDI to African countries. The reason for undertaking the study is because of the proven benefits of FDI to the host country, which include economic growth, enhanced industrialisation capacity, human capital development, and technological spillover, amongst others. It is thus considered important to investigate the role of capital market development on the attractiveness of Africa to inflow of FDI. In this study, we presented material on the measurable indicators and determinants of FDI flow. Most of the documented studies argue that FDI flows to countries with high purchasing power, better infrastructure, resource endowment and developed human capital. The role of capital market development on inflow of FDI is rarely researched. In addition, there is no documented study yet that investigates the role of capital market development on inflow of FDI on regional basis in Africa. More importantly, the importance of institutional framework to capital market development in Africa has not been documented. Further, documented studies on the role of institutional framework on the attractiveness of Africa to inflow of FDI are rare, and studies that look at these dynamics on regional basis are rare. This study fills these missing gaps in the academic literature. Using annual data from iii various sources from 1980 to 2012 in a dynamic panel environment, the findings of the study are as follows: Capital market development is an important determinant of inflow of FDI to Africa. Specifically, the financial resources provided to the private sector by domestic money banks as a share of GDP, equity capitalisation, stock turnover rate, and claims on domestic real nonfinancial sector by the Central Bank as a share of GDP are important determinants of inflow of FDI to Africa. This finding is also corroborated by the regional analysis. Further, this study establishes the importance of institutional framework on capital market development in Africa, especially corruption, the rule of law, regulatory quality, inflation as well as polity. Furthermore, it is suggested, through the impulse response approach, that one standard deviation innovations shock on capital market variables would lead to moderate improvement on inflow of FDI to the selected African countries in the short run and the improvement becomes more substantial in the long run. Similar result is recorded for the regions as well. The impulse response result also suggests that the regulatory quality in the selected African countries as well as the regions is weak. The finding indicates that one standard deviation innovations shock on this variable will negatively affect inflow of FDI and the development of capital market. The negative effects are smaller in the short run as compared to the long run. Further, improvement in corruption perception, political environment and the rule of law, in general, are found to positively influence capital market development as well as the attractiveness of Africa to inflow of FDI. The causality tests that attempt to ameliorate shortcomings regarding institutional framework may enhance the development of capital market on the continent. In addition, one of the most important components of the capital market (BANK)) is also found to directly Granger cause the inflow of FDI to Africa. Incidence of corruption, rule of law and the quality of regulatory framework are also identified as the most important institutional frameworks that determine the attractiveness of Africa to inflow of FDI. The study thus suggests the need for African countries to initiate policies that are capable of improving the institutional environment as a way of enhancing the efficiency of the capital market, and ultimately, enhance the attractiveness of the continent to inflow of FDI.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014.